Newborn signal functions in Bangladesh: identification through expert consultation and assessment of readiness among public health facilities—study protocol using Delphi technique. Issue 9 (1st September 2020) - Rahman, Ahmed Ehsanur; Banik, Goutom; Mhajabin, Shema; Tahsina, Tazeen; Islam, Md. Jahurul; Uddin Ahmed, Farid; Islam, Mushair Ul; Mannan, Md Abdul; Dey, Sanjoy Kumer; Sharmin, Shamina; Mehran, Fida; Khan, Mahbuba; et al.
Abstract : Introduction: There is a set of globally accepted and nationally adapted signal functions for categorising health facilities for maternal services. Newborn resuscitation is the only newborn intervention which is included in the WHO recommended list of emergency obstetric care signal functions. This is not enough to comprehensively assess the readiness of a health facility for providing newborn services. In order to address the major causes of newborn death, the Government of Bangladesh has prioritised a set of newborn interventions for national scale-up, the majority of which are facility-based. Effective delivery of these interventions depends on a core set of functions (skills and services). However, there is no standardised and approved set of newborn signal functions (NSFs) based on which the service availability and readiness of a health facility can be assessed for providing newborn services. Thus, this study will be the first of its kind to identify such NSFs. These NSFs can categorise health facilities and assist policymakers and health managers to appropriately plan and adequately monitor the progress and performance of health facilities delivering newborn healthcare. Methods and analysis: We will adopt the Delphi technique of consensus building for identification of NSFs and 1–2 indicator for each function while employing expert consultation from relevant experts in Bangladesh. Based on the identified NSFs and signal function indicators, the existing health facility assessment (HFA) tools will be updated, and an HFA survey will be conducted to assess service availability and readiness of public health facilities in relation to the new NSFs. Descriptive statistics (proportion) with a 95% CI will be used to report the level of service availability and readiness of public facilities regarding NSFs. Ethics and dissemination: Ethical approval was obtained from Research Review and Ethical Review Committee of icddr, b (PR-17089). Results will be disseminated through meetings, seminars, conference presentations and international peer-review journal articles.